Penyelesaian Sengketa Konsumen Di Lembaga Badan Penyelesaian Sengketa Konsumen (BPSK) Kota Samarinda - Yatini, S.H; Wahyuni Safitri (Yuriska: Jurnal Ilmiah Hukum, 2015)
Consumer Settlement Board, known as BPSK is a non-structural institution to resolve the consumer dispute out of court, BPSK itself is housed throughout the County and City which membership consists of elements of the government, consumers, and businesses. The number of cases or consumer problems, especially in the city of Samarinda start from the taps, electricity, leasing, and banking always decorate the daily media, the not active of BPSK as an intermediary between the consumer and the business agent especially in East Kalimantan makes the settlement of consumer dispute is less effective because of inadequate or the lack of human resources and the reluctance of local governments to commit the funding. Thus, whether the implementation of dispute resolution itself is effective by consumers themselves through BPSK city of Samarinda.